Indeks Pembangunan Gender Indonesia: Antara Peningkatan Angka dan Kesenjangan Substansial - Indra Kertati; Christine Diah Wahyuningsih (Universitas 17 Agustus 1945 Semarang, 2026)
The Gender Development Index (GDI) is a key indicator for assessing disparities in human development achievements between women and men. In recent years, Indonesia’s GDI has shown a consistent upward trend, reaching 91.85 in 2024. Nevertheless, this numerical improvement does not fully represent the achievement of substantive gender equality. This article aims to analyze the dynamics of Indonesia’s GDI by positioning it within a comparative Asian context and examining the substantive gaps that persist behind the rising indicators. This study employs a qualitative approach based on secondary data and literature review. The primary data sources include publications from Statistics Indonesia on the Gender Development Index and Gender Inequality Index for the 2020–2024 period, as well as the Global Gender Gap Reports 2024 and 2025 published by the World Economic Forum. Descriptive quantitative analysis is combined with qualitative interpretation and illustrative interview findings from civil society organizations, universities, and provincial and local Offices of Women’s Empowerment and Child Protection in Central Java, Southeast Sulawesi, Grobogan Regency, and Semarang City. The findings indicate that Indonesia’s GDI improvement is largely driven by advances in women’s health and educational attainment. However, substantial gaps remain in the economic dimension, particularly in per capita expenditure and women’s labor market participation, which constrain proportional improvements in women’s Human Development Index. This article underscores the importance of interpreting the GDI as a reflective policy instrument and advocates for structural transformation to ensure that numerical progress translates into genuine gender justice.